Financial Accounting and Management Accounting Training for MSMEs at the Annisa Bandung Cooperative - Tripalupi, Ramadhani Irma (Teumulong: Journal of Community Service, 2023)
One of the internal problems faced by MSMEs is that the transaction records is still extremely simple, and many have not even done that yet. 85.19% of MSMEs in the Annisa Bandung Cooperative do not carry out accounting records in an orderly manner. However, it is important for MSMEs to carry out the accounting recording process to support the fluidity of their business activities. For this reason, it is important to hold training, that aim to provide knowledge and understanding of financial and management accounting so that MSME practitioners be able to apply it to their business activities. The methodology used in community service activities in the form of training is a service learning approach. Meanwhile, the implementation method is preparation, implementation and evaluation. The results of the training activities, namely that the level of knowledge of participants increased by 34% and the level of understanding increased by 44.44%, were said to be successful because this value reached more than 25%. Participants will apply the accounting records that are trained in their business activities as follows: (1) cash flow as much as 48.16%, (2) cash flows, profit and loss statements and inventory books as much as 44.44% and (3) inventory books as much as 7.4%.